Management of the acute painful crisis in sickle cell disease‐ a re‐evaluation of the use of opioids in adult patients. (18th April 2014) - Telfer, Paul; Bahal, Nawal; Lo, Alice; Challands, Joanne
Summary: Management of the acute painful crisis (APC) of sickle cell disease (SCD) remains unsatisfactory despite advances in the understanding and management of acute pain in other clinical settings. One reason for this is an unsophisticated approach to the use of opioid analgesics for pain management. This applies to haematologists who are responsible for developing acute sickle pain management protocols for their patients, and to health care staff in the acute care setting. The objective of this article is to evaluate the evidence for use of opioids in APC management. We have highlighted the possibilities for improving management by using alternatives to morphine, and intranasal (IN) or transmucosal routes of administration for rapid onset of analgesia in the emergency department (ED). We suggest how experience gained in managing acute sickle pain in children could be extrapolated to adolescents and young adults. We have also questioned whether patients given strong opioids in the acute setting are being safely monitored and what resources are required to ensure efficacy, safety and patient satisfaction. We also identify aspects of care where there are significant differences of opinion, which require further study by randomized controlled trial.